Functoriality and K-theory for GLn(R) - Mendes, S. (2017)
We investigate base change and automorphic induction C/R at the level of K-theory for the general linear group GLn(R). In the course of this study, we compute in detail the C-algebra K-theory of this disconnected group. This article is the archimedean companion of our previous article [12].